The Role of Employee in Information Security Risk Management - Lau Keat Jin, David; Hafizah Hassan, Noor; Maarop, Nurazean; Narayana Samy, Ganthan; Che Mohd Yusof, Rasimah (International Journal of Engineering and Technology, 2018)
Information security risk management (ISRM) is become essential for establishing safe and reliable environment for online and e-transactional activities. With the coming Industrial Revolution 4.0, there is a huge interest of the organization for involving user in their risk management activity to minimize any security incidents. Limited research has been conducted in investigating involvement of user in ISRM. Therefore, this paper examines the involvement of user in ISRM in financial organization. Besides, this paper discusses the existing theories of risk management use in assessing ISRM. This paper investigates user participation in ISRM implemented in the organization using mixed-method approach. This study use questionnaire survey and follow-up with interview in one financial organization. Besides, Strength, Weakness, Opportunities and Threat (SWOT) analysis is presented based on the result found for the organisation to focus on their improvements needed. This study shows that a well-known procedure and standards must be implemented in the organisation to ensure that employee participate more in the ISRM process and activities.Â Â